P6.058 Universal HIV Screening of Inmates in Israeli Prisons: Should the Policy Be Updated?. (13th July 2013) - Mor, Z; Vider, H; Grotto, I; Aurkin, D Tischler
Abstract : Background: HIV rates among inmates are mostly higher than the general population. Israel is a relative low-HIV prevalence country (107:100, 000 population, 2011 data). All criminal inmates incarcerated in prisons/gaols at the Israeli Prison Services (IPS) are routinely screened for HIV. This retrospective study evaluates the necessity of the current policy of universal HIV-testing policy. Methods: We reviewed all inmates diagnosed with HIV/AIDS upon incarceration in Israel between 2003 and 2010, and assessed their risk-behaviours and the date of diagnosis. Results: During the 8 years follow-up, 108, 866 new criminal inmates were incarcerated in 31 correctional facilities, and it is estimated that 95% of those were tested for HIV. Of those, 201 (0.2%) were tested positively with HIV, in a direct testing cost of 622, 000 (US$). Of all 201 HIV-infected inmates, 118 (58.7%) were intra-venous drug-users (IVDU), 55 (27.4%) originated in high-prevalence countries, 13 (6.5%) were men who have sex with men (MSM), 12 (6.0%) were heterosexuals not originating in endemic country, 2 (0.1%) the risk-group was undetermined and one (0.5%) was infected vertically. Of all 201 HIV-infected inmates, 157 (78.2%) were diagnosed in the community, prior to their imprisonment, and were re-tested in prison; while 44 (21.8%) were firstly diagnosed in prison. Of those 44 inmates, 25 (56.8%) were IVDU, 13 (29.5%) originated in endemic country, three (9.1%) were MSM and in two (4.5%) the risk-group was not determined. Conclusion: HIV-infection rate is prison is twice higher than the general population. The majority (98.5%) of all inmates was diagnosed prior to their incarceration or had a key risk-behaviour exposing them to HIV. Therefore, questioning each new inmate upon incarceration about previous HIV-diagnosis, and targeted testing for other inmates who are IVDU, MSM or originating in endemic countries for HIV can detect almost all HIV-infected prisoners, presuming they respond reliably.